2015
DOI: 10.1007/s00431-015-2618-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal use of probiotics during pregnancy and effects on their offspring’s health in an unselected population

Abstract: Probiotics are used by women in the perinatal period and may improve balance of microbiota, with possible health benefits for both mother and baby. Characteristics and (health) behaviour patterns of mothers using probiotics during pregnancy, and health effects on their offspring, were investigated. Differences between mothers using probiotics during pregnancy and those who did not, were assessed. In total, 341 out of 2491 (13.7 %) mothers reported use of probiotics during pregnancy. There were no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In particular, women of reproductive age are prone to use these products for gastrointestinal symptoms [10]. Another important catchment area is represented by pregnant women, as it is estimated that up to 1 woman out of 7 in the Netherlands regularly use probiotics during gestation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, women of reproductive age are prone to use these products for gastrointestinal symptoms [10]. Another important catchment area is represented by pregnant women, as it is estimated that up to 1 woman out of 7 in the Netherlands regularly use probiotics during gestation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Women of childbearing age are one of the commonest groups to take probiotics for gastrointestinal symptoms [ 7 ]. Among pregnant women, 1.3 to 3.6% use probiotics in the United States and Canada, and up to 13.7% do so in the Netherlands [ 8 , 9 ]. It has been speculated that probiotics might help prevent preterm birth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…65 Lastly, in a study of 2,491 women, 13.7% of whom used self-prescribed probiotics, no improvement in pregnancy outcomes was found. 66 Interestingly, in light of the mixed data on these probiotic treatment trials, emerging studies in east Africa have suggested that the development and cultivation of locally grown fermented foods and probiotic cultures may be an emerging alternative prophylactic practice aimed at providing protection for illness or toxin exposure and an alternative approach to therapeutic administration of probiotics and/or prebiotics. [67][68][69][70] Necrotizing enterocolitis.…”
Section: Infantile Risk Factors and Diseases Associated With Microbiomentioning
confidence: 99%